2016
DOI: 10.3390/s16122138
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Full-Body Poses Using Only Five Inertial Sensors: An Eager or Lazy Learning Approach?

Abstract: Human movement analysis has become easier with the wide availability of motion capture systems. Inertial sensing has made it possible to capture human motion without external infrastructure, therefore allowing measurements in any environment. As high-quality motion capture data is available in large quantities, this creates possibilities to further simplify hardware setups, by use of data-driven methods to decrease the number of body-worn sensors. In this work, we contribute to this field by analyzing the capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(80 citation statements)
references
References 20 publications
3
72
2
3
Order By: Relevance
“…Of particular concern are the battery capacity and memory constraints of current wearables. Of the more popular wearable sensors, gyroscopes are notorious for limiting long-term capture due to their power requirements and would thus limit immediate application of several methods reviewed [37,[63][64][65][67][68][69]. Alternatively, accelerometers and sEMG are able to provide continuous recording for at least 24-hours with current battery technology.…”
Section: Concerns For Practical Implementationmentioning
confidence: 99%
“…Of particular concern are the battery capacity and memory constraints of current wearables. Of the more popular wearable sensors, gyroscopes are notorious for limiting long-term capture due to their power requirements and would thus limit immediate application of several methods reviewed [37,[63][64][65][67][68][69]. Alternatively, accelerometers and sEMG are able to provide continuous recording for at least 24-hours with current battery technology.…”
Section: Concerns For Practical Implementationmentioning
confidence: 99%
“…However, the model has the advantage of a relative simplicity. This allows future investigators to develop a similar algorithm based on wearable sensor data to produce equivalent output: recent papers showed that algorithms merging magnetic, inertial and eventually GPS data from multi-sensor systems can potentially provide the information required to run the algorithm in outdoor conditions (Riaz et al, 2015;Wouda et al, 2016).…”
Section: Practical Implicationsmentioning
confidence: 99%
“…There is already evidence that jerk is abnormal in PD (Teulings et al, 1997;Hogan and Sternad, 2009). Other methods of data reduction by feature extraction involve signal processing methods, e.g., wavelet analysis (Joshi et al, 2017), stochastic models, like the Hidden Markov Model (Joshi et al, 2017), or machine-learning algorithms (Wouda et al, 2016), i.e., using Random Forests (Wahid et al, 2015;Kuhner et al, 2016Kuhner et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%